2023
DOI: 10.22514/jomh.2023.028
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of physical activity is associated with better walking ability and fall-related fitness of older adults during COVID-19 in China

Abstract: This study analyzed the relationship of physical activity levels with walking ability and fall-related fitness in older adults in the Henan Provence, China. Physical activity levels of 288 older adults were assessed using the short form of the International Physical Activity Questionnaire. The participants were divided into low (LPAG, n = 81), moderate (MPAG, n = 106), and high physical activity groups (HPAG, n = 101). The 10-m walking test (10MWT), 3-m backward walking (3MBW), and Berg Balance Scale (BBS) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Regarding physical performance, de Araújo Amaral et al [16] reported that higher levels of moderate to vigorous physical activity led to higher handgrip strength (HGS) (OR = 1.75; 95%CI = 1.08 to 2.84; p = 0.007) in Brazilian older people. However, in a study by Chen et al [17], it was reported that physically inactive (PI) older people had a poorer performance in timed up-and-go (TUG; p < 0.01) and walking ability (p < 0.01) compared to the physically active (PA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding physical performance, de Araújo Amaral et al [16] reported that higher levels of moderate to vigorous physical activity led to higher handgrip strength (HGS) (OR = 1.75; 95%CI = 1.08 to 2.84; p = 0.007) in Brazilian older people. However, in a study by Chen et al [17], it was reported that physically inactive (PI) older people had a poorer performance in timed up-and-go (TUG; p < 0.01) and walking ability (p < 0.01) compared to the physically active (PA).…”
Section: Introductionmentioning
confidence: 99%
“…Although reputable reports have indicated the association between physical activity habits and better cardiometabolic variables, body composition, and physical performance in older people [10,[13][14][15][16][17], it is still necessary to understand the physical activity habits post-COVID-19 pandemic and their relationship with health status in the local population. Therefore, the main aim of this study was to associate physical activity habits (PA vs. PI) with cardiometabolic variables (blood pressure, fasting glucose, HDL cholesterol, and triglycerides), body composition (body fat percentage and fat-free mass), and physical performance (HGS, TUG, and walking speed) in Chilean older women.…”
Section: Introductionmentioning
confidence: 99%